Choosing the gender and skill of politicians: list composition and electability across Brazilian municipalities - Ferro, Adriana (2016)
This work project studies the effect of variations in the proportion of female candidates on the quality of politicians. This effect was divided between nominated and elected body. Cross-sectional data was used for two elections, and an OLS as an IV approach. Results show that the existence of female candidates on parties’ list increases the quality of the nominated body. Moreover, contrary to what many advocate, increasing the presence of female candidates either increases or has no effect on the quality of the elected body. Results that were confirmed for the overall data and controlling for region factors only.